Pragmatics and the Translation of Self-Help Discourse - Al Shandouri, Eiman S. (2016)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Eiman S. Al Shandouri entitled, "Pragmatics and the Translation of Self-Help Discourse," submitted in December 2016. Thesis advisor is Dr. Ahmed Ali. Soft and hard copy available.